Factors influencing group brainstorming performance in industrial design practices / Amer Shakir Zainol - Zainol, Amer Shakir (2010)
Generally, brainstorming is the most popular technique employed by organizations and institutions to generate creative ideas. Without exception, in industrial design practices, particularly in Malaysia, group brainstorming is also a tool that is much preferred by designers to elicit creative ideas. However, most empirical studies focus more on individual creativity rather than group creativity even though in industrial design practices it admits that group creativity, which is brainstorming, is very important. Based on past studies, this study identifies factors influencing brainstorming especially in industrial design practices. This study also attempts to enrich previous model of Input (personality traits) - Process (production loss and Satisfaction) - Output (group brainstorming performance) and brainstorming models to include Ownership of the Topic factor. This study examines four main factors, personality traits, production loss, Satisfaction, and Ownership of the Topic, all of which influence performance in group brainstorming. Personality traits in this study are based on A Big Five. Production loss is referred to as the factors that act to impair group performance. Production loss includes activities such as Production Blocking, Social Loafing, and Evaluation Apprehension. Satisfaction reflects how group members feel satisfied when they are in the brainstorming group, while Ownership of the Topic relates to the interest of individual in engaging the brainstorming activities in industrial design issue. Group performance is measured based on the Quantity of Ideas produced by the Industrial Design undergraduates during brainstorming sessions.